Variations on Reservoir Parameters of Oil Shale Deposits under Periodic Freeze-Thaw Cycles: Laboratory Tests. (16th November 2021) - Li, Rui-heng; Sun, Zhong-guang; He, Jiang-fu; Liao, Zhi-wei; Li, Lei; Qian, Fang
Abstract : As one of the most important unconventional hydrocarbon resources, the oil shale has been extracted with a frozen wall to successfully increase the shale oil production and reduce environmental pollution, which results from the harmful liquids in the in situ conversion processing of oil shale. Thereby, the strength and permeability of the frozen wall are extremely critical to reduce the harmful chemicals leaching into the groundwater. However, the permeability and strength of the frozen wall can be influenced by periodic freeze-thaw cycles. In order to investigate the damage and deterioration characteristics of oil shale samples after various periodic freeze-thaw cycles, the oil shale samples were periodically frozen and thawed as many as 48 times, after which the sample mass, stress-strain, freeze-thaw coefficient, uniaxial compressive strength, elastic modulus, and longitudinal wave velocity of the oil shale samples were separately measured. According to the measured results, the number of freeze-thaw cycles greatly influenced the physical and mechanical properties of oil shale samples. The uniaxial compressive strength and elastic modulus of the oil shale samples were changed with maximum variation rates of 64% and 65%, respectively. Meanwhile, the freeze-thaw coefficient of measured oil shale samples exponentially decreased with the increased number of freeze-thaw cycles, whereas the longitudinal wave velocity of tested samples ranged from 1602 m/s to 2464 m/s as a result of the new micropores inside the oil shale sample. Research results have enormous significance to the efficient and safe in situ exploitation of oil shale deposits.